NIR‐I Activated Orthogonal NIR‐IIb/c Emissions in a Lanthanide‐Doped Nanoparticle for Fluorescence Imaging and Information Encryption - Qiqing Li; Yuanping Huang; Haoyu Zhu; Yaqi Zhu; Yuexi Yi; Xiaodan Li; Haoran Chen; Bin Li; Dabing Li; Yulei Chang (Advanced Science)
Abstract Applying the orthogonal principle for distinguishable second near‐infrared (NIR‐II) emissions has brought new dimensions for ratio fluorescence imaging (RFI) detection and information encryption, deepening the tissue detection depth and improving signal‐to‐noise ratio and information security. However, the orthogonal NIR‐II emissions underlying these advanced optical applications have been reported only in heterogeneous structures and mixtures, limiting their practicality and potential impact. Herein, NIR‐I‐activated orthogonal NIR‐IIb/c (1530/1825 nm) emissions nanoparticles (ONNPs) are developed by spatially separated doping of Tm3+ and Er3+ emitter upon switching 808 and 980 nm excitations. RFI techniques and orthogonal NIR‐II emission ONNPs are used to demonstrate vessel depth detection based on wavelength‐dependent optical attenuation properties in tissue. The superiority of the optical coding and encoding process in a 4 × 1 binary matrix is demonstrated for anticounterfeiting and decryption imaging of quick‐response (QR) code for information storage. The research progress of this NIR‐II orthogonal emissions probe will drive the development of biomedical sensing, imaging safety, and future biophotonics technologies.